PEMILIHAN NODE TETANGGA YANG HANDAL DENGAN MEMPERHITUNGKAN SIGNAL STRENGTH DAN LINK QUALITY PADA ZONE ROUTING PROTOCOL DI LINGKUNGAN MANET - Indra Iswara, Ida Bagus Ary; Wibisono, Waskitho (Jurnal Ilmu Komputer, 2013)
Zone Routing Protocol (ZRP) is a hybrid routing protocol on MANET, because the routing protocol isbase on two protocols, namely IntrAzone Routing Protocol (IARP) and IntErzone Routing Protocol (IERP).Through IARP, each node identifies distance to all nodes in its routing zone. Although the network is very large,the update process is only distribute locally in its routing zone only and not the whole network. While IERPprotocol is responsible to find a route to a node that is located outside the zone. The selection of neighboringnodes completely done by Neighbor Discovery Protocol (NDP), which is performe by the node selection NDP issending beacons broadcast message. NDP only use TTL to decide whether the neighboring nodes in broken ormaintained.In this research, the method of signal strength based link-sensing stability adaptation into the work processof the NDP. This method works based on the signal strength of a node. Signal strength of a node are reliableif the node does not exceed the predetermined threshold value. Reliable nodes that will be stored in theneighbor table and will be a reference to the IARP routing process. Nodes are not reliable will be disconnectedand will not send beacons at the message again.The selection of reliable neighbor nodes by calculating signal strength and link quality is able to improvethe performance of ZRP routing protocols. Protocols tested in scenarios designed by the wide variationarea. The test results showed an increase of 4:13 kbps increase in throughput, a decrease of 9.98 ms e2e delayand routing overhead decreased by 3.83%.
Keywords: MANET; ZRP; Link Quality; Signal Strength; JiST/SWANS